Tesla - Colby, Jennifer, 1971- (Colby, Jennifer, 1971- Floored! Supercars., 2023)
Explores the history and development of Tesla automobiles, and highlights how Tesla is changing the automobile industry by being the only car company to focus on all-electric vehicles. Includes color photographs, fact boxes, a timeline, a glossary, and additional resources.